Visages Presents. - Bernard, Charles (Brussel : Jeunesses Plastiques et Littéraires, 1951)
Bertrand, Gaston ; Coutaud, Lucien ; Desnoyer, François ; Georg, Edouard ; Herold, Jacques ; Herbin, Auguste ; Kisling, Moïse ; Lhote, André ; Permeke, Constant ; Servranckx, Victor ; Suros ; Tailleux, Francis ; Thevenet, Louis ; Van Lint, Louis ; Venard, Claude ; Villon, Jacques ; de Waroquier, Henri ; Devos, Léon
Visages Présents, Knokke, 14 août au 15 septembre 1951
boek